Synthesis of (Z) -2 - ((pyridin-4-yl) methylene) - [1,3] dioxolo [4,5-f]-indolin-3-one and (Z) -2 - ((pyridin- 2 -yl) methylene) - [1,3] dioxolo [4,5-f]-indolin-3-one, Rhodium Coordination, and their catalytic activity in the hydroformylation of allyl hom (Revista de Investigaciones Universidad del Quindío, 2013)
This paper reports the synthesis of new complexes [RhCl(ƞ4-1,5-COD)(N-het)] where the N-het are derivatives of pyridine-indolinone, (Z)-2-((pyridin-4-yl)methylene)-[1,3]dioxolo[4,5-f]-indolin-3-one (1) and (Z)- 2-((pyridin-2-yl)methylene)-[1,3]dioxolo[4,5-f]-indolin-3-one (2), the spectroscopic data are consistent with the pyridyl coordination indolinone through pyridine nitrogen. Furthermore, indolinone pyridyl are excellents donor σ and a poor π. acceptor. The complexes showed downfield shifts of the signals of the pyridine ring in NMR. Studies of the hydroformylation of allyl and propenilbencenos showed that the rhodium complexes with pyridyl-indolinone was very active. Additionally, the complexes presented competitive reactions between the hydroformylation and isomerization.
Keywords: Hydroformylation; rhodium; pyridyl-indolinones; Eugenol; Isoeugenol; 4-anisole; trans-anethole